SURVEY OF THE PEARL BANKS, GULF OF MANNAR, 1955 - Sivalingam, S (Indian Journal of Fisheries, 2016)
The Pearl Banks of the Gulf of Mannar (Fig, 1) have been productive forcenturies. They are noted, however, for the wide fluctuations in the amount of oysters they produce: many barren years occur between productive years.The biology of the pearl oyster {Pinctada vulgaris^) as well as the historyand other features of the fishery were thoroughly investigated by Herdmanand his associates